Changes in the Share of Wealth Held by Top Wealth-Holders, 1922-1956 - Lampman, Robert J. (The Review of Economics and Statistics, 1959)
T HIS paper presents estimates derived from federal estate tax data of the numbers of top wealth -holders 1 and of the aggregate amounts of wealth held by them for selected years between I922 and I 956. Changes in the concentration of wealth during that period are delineated by relating the numbers of top wealthholders to the population and the amount of wealth held by the top group to independent estimates of the amount of wealth held by all persons. The discussion is organized under the following headings: (I) History of Wealth Distribution Study; (2) Sources of Data and Methods of Estimation; (3) The Share of Top Wealthholders in I953; (4) A Comparison with Survey of Consumer Finances for I953; (5) Historical Changes in Inequality; (6) Comparison with Wealth Distribution in England and Wales; and (7) Summary.